1978
DOI: 10.1139/z78-140
|View full text |Cite
|
Sign up to set email alerts
|

Respiration and circulation in an apodan amphibian

Abstract: Respiration and circulation were studied in the aquatic apodan amphibian Typhlonectes compressicauda (order Oymnophiona). The animals tolerate the often hypoxic and hypercapnic nature of their habitat by means of large blood volumes (25% body weight), high haemoglobin levels (11.28 g/100 ml blood), and a low P50 (22.2 mmHg (1 mmHg = 133.322 Pa)). The Bohr effect is negligible and the effects of haemoglobin concentration on the CO2 dissociation curve are discussed. Partial pH compensation in induced hypercapnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…pH/CO 2 levels (approximately 2·Pa) in burrowing cane toads whose nares were open to the air while the skin was surrounded by sand at 25°C for six·days (Boutilier et al, 1979b). Boutilier et al state that it is not uncommon for cane toads to encounter hypercapnic conditions in their environment (Boutilier et al, 1979a), including hypercapnic waters in the tropics (Toews and Macintyre, 1978). Investigations such as the current study offer insight into fundamental mechanisms of respiratory plasticity and may be of value in predicting how environmental changes such as increased atmospheric CO 2 may affect physiological function.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…pH/CO 2 levels (approximately 2·Pa) in burrowing cane toads whose nares were open to the air while the skin was surrounded by sand at 25°C for six·days (Boutilier et al, 1979b). Boutilier et al state that it is not uncommon for cane toads to encounter hypercapnic conditions in their environment (Boutilier et al, 1979a), including hypercapnic waters in the tropics (Toews and Macintyre, 1978). Investigations such as the current study offer insight into fundamental mechanisms of respiratory plasticity and may be of value in predicting how environmental changes such as increased atmospheric CO 2 may affect physiological function.…”
Section: Discussionmentioning
confidence: 73%
“…The respiratory physiology of this species has been well studied and these animals can encounter chronic hypercapnia in their natural environment (Boutilier et al, 1979a;Toews and Macintyre, 1978). In vitro brainstem-spinal cord preparations, in which vagal motor output was used as an index of breathing (fictive breathing), were used to assess respiratory-related central pH/CO 2 chemosensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…An obvious question is whether it contributes to separation of pulmonary and systemic venous blood streams. In Typhlonectes , which has a right atrial septum, Toews & MacIntyre () found that systemic arterial blood had a higher oxygen tension than pulmonary arterial blood showing some capacity for intracardiac blood stream separation. However, to our knowledge this is all that is known of intracardiac shunting in caecilians.…”
Section: Discussionmentioning
confidence: 99%
“…Maina & Maloiy, 1988). However, in aquatic Typhlonectes compressicauda , as many as three lungs develop (Toews & MacIntyre, 1978). The lungs of caecilians are internally subdivided, forming air cells that are supported by diametrically placed trabeculae.…”
Section: Structure and Function Of Certain Gas Exchangersmentioning
confidence: 99%